1997
DOI: 10.1016/s0896-6273(00)80371-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-2, a Novel Member of the Neuropilin Family, Is a High Affinity Receptor for the Semaphorins Sema E and Sema IV but Not Sema III

Abstract: Semaphorins are a large family of secreted and transmembrane proteins, several of which are implicated in repulsive axon guidance. Neuropilin (neuropilin-1) was recently identified as a receptor for Collapsin-1/Semaphorin III/D (Sema III). We report the identification of a related protein, neuropilin-2, whose mRNA is expressed by developing neurons in a pattern largely, though not completely, nonoverlapping with that of neuropilin-1. Unlike neuropilin-1, which binds with high affinity to the three structurally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
501
1
4

Year Published

2000
2000
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 612 publications
(525 citation statements)
references
References 38 publications
19
501
1
4
Order By: Relevance
“…It is unlikely, given the low binding affinity of Sema3A for NPN2 (Chen et al, 1998) that this expression serves to separate these two cell populations. This finding may be the function of the low level of expression of Sema3F, the preferred ligand for NPN2 (Chen et al, 1997;Giger et al, 1998) in the arch periphery (Fig. 2P).…”
Section: Branchial Arch Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unlikely, given the low binding affinity of Sema3A for NPN2 (Chen et al, 1998) that this expression serves to separate these two cell populations. This finding may be the function of the low level of expression of Sema3F, the preferred ligand for NPN2 (Chen et al, 1997;Giger et al, 1998) in the arch periphery (Fig. 2P).…”
Section: Branchial Arch Expressionmentioning
confidence: 99%
“…Recent studies have demonstrated that Semas may also act as chemoattractants (Bagnard et al, 1998;de Castro et al, 1999;Polleux et al, 2000). A transmembrane protein, neuropilin-1 (NPN1) has been demonstrated to be a receptor for Sema3A Kolodkin et al, 1997) whereas the related molecule NPN2 was found to bind Sema3C and Sema3F (Chen et al, 1997(Chen et al, , 1998Giger et al, 1998). NPN1 forms a homodimeric receptor for Sema3A, NPN2 does likewise for Sema3F and they act in concert to form a heteromeric receptor for Sema3C (Chen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The spatiotemporal expression patterns of Slit-2, SEMA 3B and SEMA 3F in the embryonic mouse spinal cord suggest that Slit-2 and SEMA 3B are good candidates for mediating the repulsive activity associated with the floor plate, while SEMA 3F may account for the inhibitory activity associated with the ventral spinal cord (Zou et al, 2000). Interestingly, mice deficient in NPN-2, a high affinity receptor for SEMA 3B and SEMA 3F (Chen et al, 1997), exhibit pathfinding defects that are consistent with commissural axons encountering repulsive guidance cues in the floor plate and within the ventral spinal cord after they cross the midline (Zou et al, 2000). While the in vitro functional results provide strong support for commissural axons selectively gaining responsive to repellent guidance cues after crossing through the floor plate, a role for NPN-2 in mediating these responses is difficult to reconcile with the observation that NPN-2 protein is expressed on both uncrossed and crossed segments of commissural axons in vivo and in vitro (see Zou et al, 2000).…”
Section: Vertebrate Spinal Cordmentioning
confidence: 99%
“…These include Slit-1, Slit-2, Slit-3 (see Brose and TessierLavigne, 2000 and references therein), NPN-2 (Chen et al, 1997), B-class ephrins (Imondi et al, 2000), Annexin IV (Hamre et al, 1996), BMP-6 (see Lee et al, 2000), and VEMA (Runko et al, 1999). Given that the roof plate, like the floor plate, is thought to be an important source of guidance cues for extending axons (Snow et al, 1990;Augsburger et al, 1999), each of these proteins may play important roles in regulating the pathfinding of axons that grow near, or across, the dorsal midline of the spinal cord.…”
Section: Novel Midline Markersmentioning
confidence: 99%
See 1 more Smart Citation